What evidence exists on the impacts of artificial light on terrestrial non-flying mammals native to Europe? A systematic map and a narrative review - Sordello, Romain; Fournier, Cindy; Tanaka, Taku; Thierry, Chloé (Frontiers in Ecology and Evolution, 2025)
IntroductionNowadays, light pollution due to the multiplication of outdoor lightings has become a worldwide disturbance for many species. A large amount of scientific literature shows that this sensory stressor has adverse effects on several taxa. However, existing reviews tend to conclude a lack of primary research on terrestrial non-flying mammals even if these organisms are highly nocturnal and frequently exposed to artificial light.MethodsTo have a more accurate overview on the available literature, we followed the guidelines proposed by the Collaboration for Environmental Evidence to perform a comprehensive evidence synthesis, focusing on the 186 terrestrial non-flying mammal species native to Europe. We searched 2 academic databases and Google Scholar for scientific and grey literature on the impacts of artificial light. We exported 6624 citations and screened 4866 articles on titles, abstracts, and then full-texts. We coded variables and extracted results for all the included studies to build a systematic database and we synthetized the data.ResultsWe collected 48 articles on 22 mammal species across 12 families, revealing a more substantial knowledge than expected. composed of 448 study units. We identified four main research hotspots that address different questions: 1/ impacts of manipulating the photoperiod; 2/ impacts of ex-situ artificial light on small mammals; 3/ impacts of in-situ outdoor lightings; 4/ impacts of global light pollution (sky glow). We described the results of the included studies in a narrative review to provide a factual overview of the findings. DiscussionThese initial results draw detrimental impacts of ALAN on circadian rhythm, behaviour, foraging or movements and ultimately occurrence, which are consistent with available literature on moonlight influence or ALAN effects on other taxa. Hence, we call for much more attention to be paid to wild terrestrial non-flying mammals in relation to this key anthropogenic driver.